Effect of resistence training in blood pressure at rest in normotensive elderly - Gurjão, André Luiz Demantova; Gonçalves, Raquel [UNESP]; Carneiro, Nelson Hilário; Ceccato, Marilia [UNESP]; Jambassi Filho, José Claudio [UNESP]; Gobbi, Sebastião [UNESP] (FapUNIFESP (SciELO), 2013)
Introduction: Resistance training (RT) has been widely used for older adults in order to minimize or reverse the deleterious effects of aging in the neuromuscular system. However, the potential benefits of RT on arterial blood pressure and resting heart rate in older adults remain controversial. Objective: To analyze the effect of eight weeks of RT on systolic blood pressure (SBP), diastolic blood pressure (DBP), mean arterial pressure (MAP) and heart rate (HR) in older women without hypertension. Methods: Seventeen women (aged 66.0 ± 5.8 years) without previous experience in RT were randomly assigned to either a training (TG, n = 10) or control (CG, n = 7) groups. Hemodynamic parameters at rest were evaluated by auscultatory method (mercury sphygmomanometer) and HR monitor (Polar), before and after eight weeks of experimental period. Results: Reduction possibly caused by RT were found only to SBP (-13.4 mmHg, p <0.01). Although significant reductions were observed for DBP and MAP, the analysis of covariance showed no interaction Group × Time significant. Conclusion: RT proved to be an effective training to promote adaptations in the cardiovascular system of older women without hypertension. Eight weeks of RT can significantly reduce resting SBP in older women.
Keywords: Aging; Cardiovascular system; Exercise